2017
DOI: 10.7202/1039787ar
|View full text |Cite
|
Sign up to set email alerts
|

La dynamique des compétences relationnelles dans le développement des entreprises à internationalisation rapide et précoce : une approche multiniveaux

Abstract: Alors qu’une part importante de la littérature sur les entreprises à internationalisation rapide et précoce (EIRP) souligne l’importance des réseaux sociaux dans leur dynamique, très peu nous est dit sur les compétences relationnelles mobilisées par ces entreprises pour initier, consolider et étendre ces réseaux sociaux à l’international. Pour combler cette lacune, nous avons entrepris un programme de recherche, dont l’objectif est d’améliorer la compréhension de la dynamique des compétences relationnelles dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Empirical results have also shown that "Born-global" is more innovative than other companies (Knight & Cavusgil, 2004). To this end, early internationalization can be triggered by technological capacities, managerial and in particular interpersonal skills (Elidrissi et al, 2017), as well as by the entrepreneur"s prior network and collaborations in general (Knight & Liesch, 2015;Paul et al, 2017). Furthermore, it is also argued in the literature that rapidly internationalizing companies are characterized by the lowest international survival rate compared to companies that have developed gradually (Sui & Baum, 2014).…”
Section: Fast and Accelerated Internationalization Approachmentioning
confidence: 96%
See 2 more Smart Citations
“…Empirical results have also shown that "Born-global" is more innovative than other companies (Knight & Cavusgil, 2004). To this end, early internationalization can be triggered by technological capacities, managerial and in particular interpersonal skills (Elidrissi et al, 2017), as well as by the entrepreneur"s prior network and collaborations in general (Knight & Liesch, 2015;Paul et al, 2017). Furthermore, it is also argued in the literature that rapidly internationalizing companies are characterized by the lowest international survival rate compared to companies that have developed gradually (Sui & Baum, 2014).…”
Section: Fast and Accelerated Internationalization Approachmentioning
confidence: 96%
“…The concept of new international companies continues to be the subject of much research and to interest more researchers in international entrepreneurship (Servantie et al, 2016). However, the absence of a unified denomination persists (Elidrissi et al, 2017).…”
Section: Fast and Accelerated Internationalization Approachmentioning
confidence: 99%
See 1 more Smart Citation